The Mediating Role of Achievement Behaviors on Motivation and Employee Performance - Retno Resawati; Nenny Rinawati (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
Human resources are essential to delivering organizational performance. Motivation is one factor that can improve employee performance. Motivated and achievement-oriented employees are more likely to set challenging goals, persist in the face of obstacles, seek opportunities for improvement, and demonstrate high levels of performance. This research investigates the mediating role of achievement behavior on employee motivation and performance. To test the research model, the author used a structured survey approach on employees at a government agency in Bandung with 126 employees. Before testing the data, the author first carried out a validity test by referring to the outer loading value of the research instrument and the cronbach alpha value, which met the testing requirements. The author uses a non-parametric approach, namely Partial Least Squares (PLS). The research results indicate that achievement thinking influences employee performance as well, and achievement behavior influences performance. The implications of the research show that employee motives, such as a strong mind, can encourage enthusiasm to carry out work optimally so that they can complete the task as well as possible. This research explores the mediating role of achievement behavior on employee motivation and performance. The research has shortcomings, namely that it is cross-sectional, so it only applies at one time and examines the impact of achievement behavior on employee motivation and performance. To strengthen these findings, further research with more representative samples is important.